SELF-CONTROL DALAM PANDANGAN AL-QUR’AN, STUDI AL-QUR’AN TEMATIK DENGAN PENDEKATAN GROUNDED THEORY - Herlina, Herlina; Alif, Muhammad; Syaefulloh, Syaefulloh (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The ability to control oneself is an important part of a psychologically and spiritually healthy personality. In modern psychology, self-control has been widely studied because it is an important component in character formation, decision making, and emotional management. However, research on the concept of self-control from the perspective of the Qur’an is still lacking and has not been systematically arranged thematically. The purpose of this study is to explore and construct the concept of self-control based on the verses of the Qur’an using the Grounded Theory approach, which allows theories to emerge inductively and contextually from the text of revelation. This study shows that self-control in the Qur’an is not only related to controlling lust and patience, but also links deep spiritual aspects such as taqwa (awareness of God), ikhlas (purity of intention), and muraqabah (awareness of God's supervision). These results will enrich research on the topic of the Qur’an, in addition, these results will offer a new conceptual framework that can be integrated, connecting Islamic values ​​with modern psychological perspectives, and offering practical assistance to help Muslims face the challenges of self-control in the modern era.